2019
DOI: 10.1128/aac.02623-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of the New β-Lactamase Inhibitors Relebactam and Vaborbactam in Combination with β-Lactams against Mycobacterium abscessus Complex Clinical Isolates

Abstract: Pulmonary disease due to infection withMycobacterium abscessuscomplex (MABC) is notoriously difficult to treat, in large part due to the intrinsic resistance of MABC strains to most antibiotics, including β-lactams. MABC organisms express a broad-spectrum β-lactamase that is resistant to traditional β-lactam-based β-lactamase inhibitors but inhibited by a newer non-β-lactam-based β-lactamase inhibitor, avibactam. Consequently, the susceptibility of MABC members to some β-lactams is increased in the presence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 38 publications
3
51
5
Order By: Relevance
“…Nacubactam and zidebactam were procured from MedKoo Biosciences, Inc., NC, USA (purity >98%). A total of twenty-six β-lactam antibiotics (Table 1), including penicillins, cephalosporins and carbapenems, were purchased from commercial sources as previously described (10). The purity of all β-lactams was >95%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nacubactam and zidebactam were procured from MedKoo Biosciences, Inc., NC, USA (purity >98%). A total of twenty-six β-lactam antibiotics (Table 1), including penicillins, cephalosporins and carbapenems, were purchased from commercial sources as previously described (10). The purity of all β-lactams was >95%.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-eight clinical isolates of MABC were collected at Johns Hopkins Hospital, Baltimore, MD, USA from 2005 to 2015 and described previously (8, 10). M. abscessus ATCC 19977 was purchased from the American Type Culture Collection (Manassas, VA, USA) and used as a reference strain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, a number of studies have been published demonstrating a number of β -lactam combinations displaying high levels of in vitro synergistic activity against M. abscessus complex (Pandey et al 2019) (Story-Roller et al 2019). Furthermore, a recent study identified the in vitro activity of two new non- β -lactam β -lactamase inhibitors, namely relebactam and vaborbactam, demonstrating synergistic activity between imipenem and relebactam as well as meropenem and vaborbactam (Kaushik et al 2019).…”
Section: Introductionmentioning
confidence: 99%